Non-communicable Diseases Week: Best Practices in Addressing the NCDs Burden from Tanzania - Belinda J. Njiro; Jackline E. Ngowi; Harrieth P. Ndumwa; Davis Amani; Castory Munishi; Doreen Mloka; Emmanuel Balandya; Paschal Rugajo; Anna T. Kessy; Omary Ubuguyu; Bakari Salum; Appolinary Kamuhabwa; et al. (Annals of Global Health, 2023)
Background: Five million people die every year from non-communicable diseases (NCDs) globally. In Tanzania, more than two-thirds of deaths are NCD-related. The country is investing in preventive and advocacy activities as well as interventions to reduce the burden. Of particular interest, the Ministry of Health (MoH) commemorates NCDs’ week using a multisectoral and multi-stakeholders’ approach. This paper highlights activities conducted during NCDs week with the aim of sharing lessons for other countries with similar context and burdens. Methods: A thorough review of official reports and the national strategic plans for NCDs was done including the 2020 and 2021 National NCDs’ week reports, the National Strategic Plan for NCDs 2015–2020, and the National NCDs agenda. Findings: NCDs week is commemorated annually throughout the country involving the five key activities. First, community awareness and participation are encouraged through media engagement and community-based preventive and advocacy activities. Second, physical activities and sports festivals are implemented with a focus on developing and renovating infrastructures for sports and recreation. Third, health education is provided in schools to promote healthy behaviors for secondary school adolescents in transition to adulthood. Fourth, health service provision and exhibitions are conducted involving screening for hypertension, diabetes, obesity, alcohol use, and physical activities. The targeted screening of NCDs identified 10% of individuals with at least one NCD in 2020. In 2021, a third of all screened individuals were newly diagnosed with hypertension, and 3% were found to have raised blood glucose levels. Fifth, the national NCDs scientific conferences conducted within the NCDs week provide an avenue for stakeholders to discuss scientific evidence related to NCDs and recommend strategies to mitigate NCDs burden. Conclusion: The initiation of NCDs week has been a cornerstone in advocating for NCDs control and prevention in the country. It has created awareness on NCDs, encourage healthy lifestyles and regular screening for NCDs. The multi-stakeholder and multi-sectoral approaches have made the implementation of the mentioned activities feasible and impactful. This has set an example for the united efforts toward NCD control and prevention at national, regional, and global platforms while considering contextual factors during adoption and implementation.